Antibrowning Compounds for Minimally Processed Potatoes: A Review. Issue 5 (3rd July 2020) - Bobo-García, Gloria; Arroqui, Cristina; Merino, Gorka; Vírseda, Paloma
ABSTRACT: This review covers some recent advances in browning prevention in minimally processed potatoes (MPP). Polyphenol oxidase (EC 1.10.3.1, PPO) is one of the main enzymes involved in browning of potatoes. Antibrowning agents are used in combination with other compounds and techniques to reduce browning such as physical treatments with modified atmospheres and cold temperatures in processing and storage. Due to increasing concerns involving toxicity from various traditional food preservatives, this review focuses on studies involving substances that have different mechanisms to control browning. These substances include reducing agents, acidulants, chelating agents, enzyme inhibitors, complexing agents or others, such as Maillard reaction products and natural extracts.